If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+12x-9=3(5x+9)
We move all terms to the left:
3x+12x-9-(3(5x+9))=0
We add all the numbers together, and all the variables
15x-(3(5x+9))-9=0
We calculate terms in parentheses: -(3(5x+9)), so:We get rid of parentheses
3(5x+9)
We multiply parentheses
15x+27
Back to the equation:
-(15x+27)
15x-15x-27-9=0
We add all the numbers together, and all the variables
-36!=0
There is no solution for this equation
| 4y^2-3y=7 | | 11m+12+5m=47+7m–8 | | 5=-6+4x | | 6s-3s=139.50 | | 8/x=4/16 | | 4X=x(x-3) | | 5=-6+x4 | | w-79=191 | | 5x-12=3x+34 | | 2x(x-10)=12 | | 2y+10=74 | | L+1+4xW=42 | | 3+7x=2x | | 5r-7=14+7 | | 5t-3=t+14 | | 11.5X-0.1x^2-150=0 | | 4=16+4{m-8} | | (50/x)+2x=4x | | x=x^2+6x=8 | | 9(y+4)=31 | | 2(x÷4)=120 | | 4x^2+6x-82=0 | | 6(9+4x)+6(2–x)=7x | | 3^4x=1/243 | | X+2x+5x+30=360 | | 250=4r+4(r+20) | | -36+k=8(-3k-5)+4 | | 8x+10=7x-15 | | 5x-7=6x+20 | | 8x+10=7x–15 | | (4m+9)/3=7-2m | | -3x/3=-12/3 |